2017
DOI: 10.11604/pamj.2017.28.189.11901
|View full text |Cite
|
Sign up to set email alerts
|

Le syndrome de Pepper: à propos de deux cas observés au Centre Hospitalier Universitaire Pédiatrique Charles de Gaulle de Ouagadougou (Burkina Faso)

Abstract: Le syndrome de Pepper est une forme métastatique hépatique du neuroblastome. C’est une entité spécifique du nourrisson de moins de six mois qui a la particularité de pouvoir régresser de façon spontanée avec un pronostic favorable dans 80% des cas. A cause de sa rareté, nous rapportons deux cas du syndrome de Pepper observés au Centre Hospitalier Universitaire Pédiatrique Charles de Gaulle de Ouagadougou (Burkina Faso). Il s’agissait de deux nourrissons de sexe féminin chez qui la symptomatologie de la maladie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…On the other hand, Adjagba et al in Benin in 2018 reported a male predominance with an M/F sex ratio of 1.3[9]. Studies carried out in Cameroon in 2022 and in Burkina-Faso in 2016 also noted a male predominance with sex ratios of 1.01 and 1.05 respectively[26] [27]. Sen et al found a male predominance of 55.8% in 2017 in a study of children with operated congenital heart disease from 17 low-and middle-income countries[28].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Adjagba et al in Benin in 2018 reported a male predominance with an M/F sex ratio of 1.3[9]. Studies carried out in Cameroon in 2022 and in Burkina-Faso in 2016 also noted a male predominance with sex ratios of 1.01 and 1.05 respectively[26] [27]. Sen et al found a male predominance of 55.8% in 2017 in a study of children with operated congenital heart disease from 17 low-and middle-income countries[28].…”
mentioning
confidence: 99%
“…[16] [26] [30][34].Surgical treatment was indicated in 86.7% of children. This finding was reported byTougouma et al and Aliku et al with respective frequencies of 86.0% and 76.0% [16] [17].…”
mentioning
confidence: 99%